THE EFFECT OF CASHEW NUT EXPORTS, GROSS DOMESTIC PRODUCT (GDP) AND EXCHANGE RATE ON INDONESIA'S FOREIGN EXCHANGE RESERVES - Saharuddin, Saharuddin (Accounting and Business Journal, 2024)
This study aims to determine the effect of cashew nut exports, Gross Domestic Product (GDP) and exchange rates on short-term and long-term foreign exchange reserves in Indonesia. The data used is a time series in the range of 1986-2021 obtained from the world bank and FAO (Food And Agriculture Organization). This study used an Autoregressive Distributed Lag (ARDL) model with 10 e-views. The results showed that in the short term cashew nut exports have a positive and significant effect on Indonesia's foreign exchange reserves while in the long term cashew nut exports have a negative and insignificant effect on Indonesia's foreign exchange reserves. The variable Gross Domestic Product (GDP) has no effect and is significant on foreign exchange reserves in the short term and in the long run Gross Domestic Product (GDP) has a positive and significant effect on foreign exchange reserves. While the exchange rate variable has no effect and is significant on foreign exchange reserves in the short term and in the long term the exchange rate has a positive and significant effect on foreign exchange reserves